TEACHERS' CONCEPTION OF ASSESSMENT FOR LEARNING IN ELT CLASSROOM IN AN INDONESIAN SCHOOL DURING ONLINE LEARNING - Ni’matul Farikhah; Endang Setyaningsih; Sumardi Sumardi (UICELL, 2021)
The current study investigates how teachers in ELT classrooms interpret the concept of Assessment for Learning (AfL) during online learning. More specifically, the research intends to see how the concept of assessment for learning can help engaged teachers get a better understanding of AfL and optimize their own usage of AfL in the classroom. This research also contributes to a better understanding of learning assessment in the context of online learning, particularly in terms of enhancing students' English learning outcomes. It also elaborates how teachers should plan their online instruction while taking into account the AfL's existing components. Two English teachers from an Indonesian junior high school participated in this study. A case study research design was used in this study. Data was gathered through interviews and questionnaires. Then, collecting data from questionnaires distributed to teachers online. Thematic analysis with coding was utilized as the analysis technique. These findings show that teachers do not properly understand the basic concept of AfL, resulting in less-than-optimal implementation in the classroom. Keywords: Assessment for Learning (AfL), ELT classroom, Online Learning